(untitled) (Research, Society and Development, 2021)
Introduction: VAP is considered one of the main infections related to health care with increasingly higher rates in an ICU, these numbers can vary from 9% to 67% of all patients on prolonged or non-extended use of mechanical ventilation. General Objective: to know the challenges faced by dentists in preventing VAP in an ICU. Methodology: To carry out this study, we opted for a research in the modality of integrative literature review. Results and Discussion: the integration of the dentist in the multidisciplinary team working in the ICUs leads to the expansion of the professional’s teaching and performance field, enabling the formulation and adaptation of guidelines and bundles, as they are the most qualified professionals in this area of knowledge. Final Considerations: The entire multidisciplinary health team allocated to the ICU’s, including dentists, must act in accordance, adopting measures to prevent VAP in order to reduce the risks for its occurrence, always following an integrated line of care, thus reducing, the death rate of their patients.